Analisis Kejadian Dismenore Pada Siswi Smp Negeri 1 Pedamaran Kabupaten Ogan Komering Ilir Tahun 2017 - Endah Novereta; Chairil Zaman (IKEMAS: Jurnal Ilmu Kesehatan Masyarakat, 2018)
Reproductive health in international conference on population development is a complete physical, mental and social well-being relating to reproduction system, function and process. For young women reproductive organs develop normally with menstuasi does not mean menstuasi show a woman has grown up but this menstruation shows the maturity of reproductive organs. Know the description of the incidence of dysmenorrhea in female students of SMP Negeri 1 Pedamaran Ogan Komering Ilir in 2017. This research uses quantitative method with cross sectional approach and analytic method. This research was conducted on January 5 to January 14, 2017 at SMP Negeri 1 Pedamaran Ogan Komering Ilir. Samples in this study were students who experienced dysmenorrhea with a total of 165 people using total sampling techniques. From result of research between some factor there is no relation between anxiety and dysmenorrhea occurrence p Value> 0,693, there is no relation between sex and hemoglobin value p value = 0.855, there is no correlation between age of menarche and incidence of dysmenorrhea Value = 0.774. From the results of the study can be concluded that there is no relationship between anxiety, nutritional status and menarche age with the incidence of dysmenorrhea. For the school of SMP Negeri 1 Pedamaran. It is expected that there will be an increase of health education for female students especially about dysmenorrhea incident.